Implementasi Peran dan Tugas Guru Dalam Kurikulum Merdeka - Indriawati, Prita; Sari, Dewi Ratna; Firda, Queen Ika Dewi Ayu Ana; Budiono, Nasywa Haniifa; Mariam, Mariam; Rakasiwi, Muhammad Rifki (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2025)
The implementation of the role and duties of teachers in the Independent Curriculum is not only limited to delivering information, but also involves the role of teachers as facilitators who not only provide motivation and inspiration to students, but are also responsible for ensuring the realization of an optimal learning process. The purpose of this study is to provide an overview of the role and duties of teachers in implementing the independent curriculum. The method used in this study uses a qualitative research method, which is interactive with data sources in order to obtain meaning. In this study, researchers used data collection techniques using literature reviews, which include studies related to various existing writings or sources, both in the form of books, journals, articles, theses and other accurate sources available from the internet. The results of this study are that the readiness of the implementation of the role of teachers and school assignments in the Independent Learning Curriculum is quite good. This can be proven by the presence of driving teachers in each school, who have a key role as leaders in bringing about positive change, improving the quality of teaching, successfully encouraging the independence of fellow teachers, forming a dynamic learning environment through discussion and collaboration, and improving the quality of student leadership in schools.